Effect of Cationic Surfactant in the Synthesis Process of Nano γ-Alumina for Petroleum Industry Application - Flayyih, mustafa H.; Theib, Mohammed S. (Journal of Petroleum Research and Studies, 2022)
Nanotechnology is widely used in industries, including catalyst synthesis for oil and gas industries to enhance and perform new Characteristics of materials. Cetyl tri methyl ammonium bromide (CTAB) cationic surfactant was used in the synthesis of spherical nanostructured γ-alumina to enhance the morphology of the prepared nano gamma alumina which is used as a catalyst support in the naphtha reforming process. The preparation was carried out by co-precipitation method by adding drop wise of ammonium hydroxide solution and aluminum nitrate nonahydrate solution simultaneously to a solution of surfactant medium, PH and temperature of reaction were kept at 8 and 30 cᵒ respectively. The gamma alumina obtained were characterized by X- Ray Diffraction (XRD), nitrogen adsorption-desorption analysis (ASAP 2020, Micromeretics) and atomic force microscope (AFM). The sample of synthesized gamma alumina with the CTAB cationic surfactant showed that surface are (314 m2/g), pore volume (0.37 cm3/g), and pore size (3.6 nm).